MODELLING, CHARACTERISATION AND INTERPRETATION OF RHEOLOGICAL EXPERIMENTS PERFROMED ON AQUEOUS SOLUTIONS OF WORM LIKE MICELLES - ADENIYI OGUNKEYE (2023)
This thesis reports a series of theoretical, experimental and computational investigations concerning advanced rheometry and the dynamics of worm like micellular systems (WLMs) in superposition rheometry. A robust experimental data set is first obtained under both parallel and orthogonal superposition rheometry conditions before the ability of the Corotational Maxwell, Giesekus and, for the first time, Gordon-Schowolter constitutive models to capture the behaviour of WLMs under superposition flows is evaluated. The initiation of stress controlled oscillatory rheometry is then investigated both theoretically and experimentally (using the same WLM system) to determine the impact of instrument inertia on the establishment of steady state oscillatory flows. This study reveals that the time scale for the establishment of steady state oscillations can be dramatically impacted by the presence of instrument inertia. Finally, a Brownian Dynamics approach is used in an attempt to identify the polymer dynamics responsible for the appearance of negative values of the ‘parallel storage modulus’ under certain conditions, as is often noted in the literature.